The Effect of Work-Family Conflict and Job Stress on Performance With Job Satisfaction As A Mediation Variable - Agus Nugroho; Soepatini Soepatini; Hari Wujoso; Jati Waskito (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2024)
This research aims to analyze the influence of work-family conflict and work stress on performance with job satisfaction as a mediating variable using quantitative research methods and SMART PLS analysis tools. 4 of the population in this study are female nurses working shifts in the ward and emergency room using a purposive sampling approach. with a sample size of 89 according to the criteria. The results of this study show that work-family conflict has a negative and insignificant effect on performance, work-family conflict has a negative and significant effect on job satisfaction, work stress has a negative and insignificant effect on performance, work stress has a negative and insignificant effect on job satisfaction, job satisfaction. work has a positive and significant effect on performance, work-family conflict has a negative and significant effect which is mediated by job satisfaction and work stress has a negative and insignificant effect on performance which is mediated by job satisfaction.